2006
DOI: 10.1038/sj.onc.1209681
|View full text |Cite
|
Sign up to set email alerts
|

Role of the interaction between large T antigen and Rb family members in the oncogenicity of JC virus

Abstract: Human polyomaviruses (JC virus, BK virus and simian virus 40) are causative agents of some human diseases and, interestingly, are involved in processes of cell transformation and oncogenesis. These viruses need the cell cycle machinery of the host cell to complete their replication; so they evolved mechanisms that can interfere with the growth control of infected cells and force them into DNA replication. The retinoblastoma family of proteins (pRb), which includes pRb/p105, p107 and pRb2/p130, acts as one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 83 publications
0
48
0
Order By: Relevance
“…16). More than 80% of neonatal hamsters inoculated intracerebrally, i.p., or s.c. with strains of JCV, isolated from progressive multifocal leukoencephalopathy lesions, develop a wide range of tumors including medulloblastomas, neuroblastomas, and pineocytomas (16,17). Although the mechanism of JCV-induced neurotumorigenesis is not entirely clear, several studies point to the involvement of the viral early protein, T antigen, in this process.…”
Section: Molecular Biology Of Medulloblastomamentioning
confidence: 99%
“…16). More than 80% of neonatal hamsters inoculated intracerebrally, i.p., or s.c. with strains of JCV, isolated from progressive multifocal leukoencephalopathy lesions, develop a wide range of tumors including medulloblastomas, neuroblastomas, and pineocytomas (16,17). Although the mechanism of JCV-induced neurotumorigenesis is not entirely clear, several studies point to the involvement of the viral early protein, T antigen, in this process.…”
Section: Molecular Biology Of Medulloblastomamentioning
confidence: 99%
“…When we used siRNAs to downregulate ICBP90 and DNMT1 expressions, we observed that pRB expression was increased in Jurkat cells and HVTs-SM1. Nevertheless, since HVTs-SM1 have inactivated pRB, due to the interaction with large T antigen (Caracciolo et al, 2006;Giacinti and Giordano, 2006), a direct involvement of pRB in the mechanism of action of ICBP90 on VEGF gene expression seems unlikely. Interestingly, downregulation of ICBP90 (present results) and DNMT1 (Fournel et al, 1999 and present is a negative regulator of the VEGF gene expression (Miki et al, 2001), we propose that the ICBP90/DNMT1 complex can control VEGF expression via a downregulation of the p16 INK4A gene.…”
Section: Icbp90 Interacts With Dnmt1 and Regulates Vegf Expression M mentioning
confidence: 99%
“…T-Ag can induce aberrant cell cycle entry and S-phase initiation in a variety of somatic phenotypes, through its binding to the tumor suppressor retinoblastoma protein (Rb) and consequent derepression of Rb targets (16,(32)(33)(34)(35). Whereas some mitotic phenotypes may undergo neoplastic transformation by this process (and the polyomaviruses have been causally linked to oncogenesis in various species and cell types; refs.…”
Section: Jcv Efficiently Infects Astroglia and Their Progenitors In Cmentioning
confidence: 99%